Analysis of Organizational Culture at Mining Company in Lahat South Sumatra - Winda Grencia Manullang; Aurik Gustomo (Interdisciplinary Social Studies, 2025)
This study analyzes organizational culture at Mining Company Lahat, South Sumatra, to understand the impact of leadership, communication, employee involvement, and training on organizational culture. Utilizing a quantitative approach and total sampling technique, the research involved 37 mechanics working at the project site. Data were collected through a structured questionnaire based on a five-point Likert scale. Results from multiple linear regression analysis indicated that all independent variables significantly influence organizational culture, with a total contribution reaching 84.2%. Priorities for improvement were identified in training and communication. This study emphasizes the importance of effective collaboration to foster a supportive organizational culture, which contributes to enhanced employee performance and organizational sustainability.